Influence of stocking density on growth, production and survival of Macrobrachium rosenbergii (de Man) in a monoculture grow-out pond - Nagarathinam, N; Kumar, J Stephen Sampath; Sundararaj, V (Indian Journal of Fisheries, 2011)
Growth and production characteristics of Macrobrachium rosenbergii stocked at two densities were examined. Prawn juveniles (0.78±0.54 g) were reared for 180 days in 0.0014 ha tanks at two stocking densities (5/m2 and 10/m2) individually. The culture tanks were manured with cowdung and inorganic fertilizers and a supplementary feed of 22% crude protein was given to the prawns. The results indicated that at low stocking density (5/m2) the growth and survival were higher. Prawns attained a final mean body weight of 31.32±21.5 g and 28.38±14.23 g in low and higher stocking densities, respectively. The estimated productions were 984.34 and 1,662.26 kg/ha per crop, respectively for two stocking densities. Higher mean growth rate, specific growth rate and low FCR were witnessed only in the low stocking density. The relationship between growth and days of culture is significant (P<0.05) in the two stocking densities but, the difference between growth rates of the prawn at the two densities tried is non-significant (P>0.05). Advantages of low stocking are witnessed with reference to individual body weight at the harvest.